Analysis of Psychological and Gut Microbiome Characteristics in Patients With Non-erosive Reflux Disease - Yang, Fan; Xie, Xin-hui; Li, Xi; Liao, Hui-na; Zou, Bing (Frontiers in Psychiatry, 2022)
Objective: To assess the correlation between the incidence of non-erosive reflux disease (NERD) and psychological factors, especially somatoform disorders. To investigate the characteristics of gut microbiome in NERD patients. Methods: We enrolled 24 NERD patients and 24 healthy controls. All patients were evaluated via GerdQ, SOMS-7, SAS, HAMA, and HAMD. Fecal samples were collected and 16S rRNA sequencing was performed to evaluate the gut microbiome composition. Results: The main symptoms of the NERD patients were regurgitation (87.5%), belching (66.7%), pharyngeal discomfort (50%), and heartburn (37.5%). The average score of GerdQ was 13.42 ± 3.41. In 15 patients (62.5%), the total score of the last two items was <3 points, while the average score of 24 patients was 3.63 ± 2.32. NERD patients with somatoform disorders accounted for 50%. There were 17 patients without anxiety, 6 patients with mild anxiety (25%), 1 patient with moderate anxiety (4.2%), and no patient with severe anxiety. There were 22 patients (91.7%) without depression, 2 patients (8.3%) with mild depression, and no patient with moderate or severe depression. The alpha diversity of NERD group was higher than HC, which showed significant difference (P < 0.05). The beta-diversity was significantly different between HC and NERD patients (P = 0.026), male and female patients (P = 0.009). The beta-diversity was also significantly different between male and female patients (P = 0.009). There were several bacteria with significant differences between HC and NERD group, and NERD patients with or without somatoform disorders, such as Firmicutes, TM7 were enriched in the NERD group compared with the healthy control group, while Bacteroidetes were enriched in the healthy controls. Conclusions: NERD symptoms overlap with somatoform disorders. NERD symptoms have an impact on the daily life quality of patients. Some of them are accompanied by anxiety and depression of different degrees, and the two are significantly correlated. The diversity of gut microbiome in patients with NERD is significantly higher than healthy controls, which has its characteristics. The predominant bacteria in gut microbiome of patients with NERD are similar to the healthy population, with Firmicutes and Bacteroidetes as the main ones. The composition of gut microbiome in NERD patients with or without somatoform disorder is significantly different, which may be related to the interaction of microbiome-brain-gut axis.